Tactile Sensation Improves Following Motor Rehabilitation for Chronic Stroke: The VIGoROUS Randomized Controlled Trial. (August 2022) - Borstad, Alexandra; Nichols-Larsen, Deborah; Uswatte, Gitendra; Strahl, Nancy; Simeo, Marie; Proffitt, Rachel; Gauthier, Lynne
Background. Up to 85% of people with chronic stroke experience somatosensory impairment, which contributes to poor sensorimotor control and non-use of the affected limb. Neurophysiological mechanisms suggest motor rehabilitation may improve tactile sense post-stroke, however, somatosensory recovery has rarely been reported in controlled trials. Objective. To compare the effect of four upper limb motor rehabilitation programs on the recovery of tactile sensation in adults with chronic stroke. Methods. Adults with chronic stroke and mild or moderate upper extremity hemiparesis ( n = 167) were enrolled in a multi-site randomized controlled trial. Participants completed three weeks of gaming therapy, gaming therapy with additional telerehabilition, Constraint-Induced Movement therapy, or traditional rehabilitation. Here, we report the results of a secondary outcome, tactile sensation, measured with monofilaments, before and after treatment, and 6 months later. Results. A mixed-effects general linear model revealed similar positive change in tactile sensitivity regardless of the type of training. On average, participants were able to detect a stimulus that was 32% and 33% less after training and at 6-month follow-up, respectively. One-third of participants experienced recategorization of their level of somatosensory impairment (e.g., regained protective sensation) following training. Poorer tactile sensation at baseline was associated with greater change. Conclusions. About one-third of individuals with mild/moderate chronic hemiparesis experience sustained improvements in tactile sensation following motor rehabilitation, regardless of the extent of tactile input in the rehabilitation program. Potential for sensory improvement is an additional motivator for those post-stroke. Characteristics of those who improve and mechanisms of improvement are important future questions.Clinicaltrials.gov NCT02631850